The mediating role of resilience in the relationship between religious struggles and health behaviours in a group of polish young adults - Boczkowska, Magdalena (Journal of beliefs and values, 2025)
The purpose of the study was to examine more thoroughly the relationship between religious struggles and health behaviours. In this study were examined the role of resilience as a potential mediator in the relationship between these variables of interest and it was focused on the polish young adult generation. Participants were 616 people aged 18–33 years (M = 25.33; SD = 7.27). The respondents indicated their gender and age, and then completed The Religious and Spiritual Struggles Scale (RSSS), The Brief Resilience Scale (BRS), and Health Behaviour Inventory (HBI). In all models, resilience was evaluated as a potential mediator between types of religious struggle and health behaviour. The mediation analysis showed that including resilience as part of the overall model weakened the negative association between the dimensions of religious struggle – divine, ultimate meaning, and doubt ¬– and health behaviour. The presented negative impact of religious struggles on health behaviour points to the need to build or strengthen resilience among individuals, with resilience as a potential buffer to both reduce the negative effect of R/S struggles and strengthen pro-health behaviour.